ลำดับชั้นหินและสภาพแวดล้อมการสะสมตัวโบราณของหินปูนไทรแอสสิกบริเวณเขำสุขไพรวัน อำเภอแกลง จังหวัดระยอง - วิลัยพร ศรีนาม (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The aim of this work is to study on lithostatigraphy and paleoenvironment of sedimentary rock exposed at Khao Sukphaiwan, Amphone Klaeng,Changwat Rayong.Three exposures have been measured and 40 samples were collected in order to study petrography and determination of carbonate rock in the study area. The section contains thin to thick bedded. The sedimentary rocks consist of limestone, shale and sandstone which the strike of bedding plane is in east-west and dipping to south. Normal graded bedding and lamination were found. Oncoid are abundant in bed of all section. The carbonate rock type contains mudstone, wackestone, packstone, grainstone. The grain consists of oncoid. Foraminifers are Endotriada and Crytoseptida were found in this study area and indicate Early Triassic. The depositional environment of limestone was in low energy such as intertidal to shallow subtidal because oncoid can be found